Monitoring of water quality : the contribution of advanced technologies - Colin, F.; Quevauviller, Ph (Elsevier, 1998)
Water can be considered as one of the basic elements supporting life and the natural environment, a primary component for industry, a consumer item for humans and animals and a vector for domestic and industrial pollution. Various European Directives already provide a framework for the control of aquatic substances, the quality of bathing, surface and drinking water and effluent control. Such regulatory measures are closely related to analytical measurements. In order to comply with these regulations on a permanent basis, treatment plants and distribution companies, as well as water users and polluters, need to implement automated measuring techniques, such as sensors and other analytical tools in continuous or sequential mode to obtain suitable alarm systems and facilitate the management of water resources and decision making processes. This approach is in continuous evolution within the European Union. In view of the consequences of wrong measurements, it is vital that reliable quality control systems be achieved and maintained. At present, only a small range of analytical parameters can be measured automatically, it is therefore necessary to develop and validate new methods to extend the list of parameters. The development of new methodologies requires that the most recent know-how in fields such as optics, electrochemistry, biochemistry, chemometrics and others be shared by experts. In order to identify possible actions to be undertaken in the field of standards, measurements and testing for monitoring water quality, the Standards Measurements and Testing (SMT) Programme of the European Union, organised a European workshop that was held in Nancy 29-31 May 1997. This workshop bought together researchers and industrial users with the aim to make an overview of the present state-of-the-art, to consider possible improvements in existing techniques and the need and possibilities of developing new advanced technologies.